The application of SWOT analysis as a basis for determining marketing strategies - Tenti Indah Lestari; Lidia Yunita (Institute of Computer Science (IOCS), 2020)
The purpose of this study was to Determine the marketing strategy of Hisana Fried Chicken's fast food business through a SWOT analysis. In Determining the marketing strategy it is Necessary to know the internal factors of strengths and weaknesses or SAP analysis, external factors of opportunities and threats or ETOP analysis. The design used in this study is descriptive qualitative. The subjects of this study were branch heads, employees and consumers. Sample of this research is branches, employees and consumers at Hisana Fried Chicken outlet, Panglima Denai. The sample technique used in this study was purposive sampling. The research instrument was Carried out by interview, observation and documentation. Analysis of the Data used is by reductio of data, the data presentation, and conclusion drawing.